FINANCIAL CRISIS AND SUSTAINABLE DEBT MANAGEMENT IN NIGERIA, 1980 – 2017 - ISRAEL ONOKERO IMIDE; RICHARDCHINYEOSADUME; Eko-Raphaels, Melvin. U; BLESSING C. UZOMAH (International Journal of Social Sciences and Management Review, 2018)
The study examined the effect of financial crisis and sustainable debt management in Nigeria. The main objective of the study is to examine financial crisis and sustainable development in Nigeria. The model built for the study has sustainable debt management (SDM) as endogenous variable and exogenous variables wasfinancial crisis (FINCR) proxied by financial Deepening (Bank Deposit to GDP ratio). Annual time series data were gathered from the Central Bank of Nigeria Statistical Bulletins from 1980 to 2017. The techniques used for analysis are the Ordinary Least Square Techniques, the Augmented Dickey Fuller Unit Root Test Techniques and the Co-integration Test. The econometric techniques of Ordinary Least Squares (OLS) results show that a positive and significant relationship exists between FINCR and SDM in the short and long run periods. The study concludes that there is a significant relationship between financial crisis and sustainable debt management in Nigeria and recommends government’s reduction of its over-dependence on other global economies for goods and services importation and development of its productive base to facilitate export trade.
Keywords: Debt Management; Financial Crisis; Gross Domestic Product.